Correlations between dermatoglyphic patterns on finger bulbs - Moszczyński, Jarosław (Anthropological Review, 2022)
Attention was focused on correlations between four basic types of dermatoglyphic patterns on finger bulbs of 3,100 men. The dominating associations were found in homologous and neighboring fingers. The most strongly correlated group of patterns proved to be whirls (W) which moreover constituted the only group to reveal no positive relations with the other types of patterns, namely arches (A), ulnar loops (Lu), and radial loops (Lj.).